Elemental and Sr-Nd-Pb-Hf isotope signatures of Early Cretaceous magmatic rocks in the Wulian area, eastern Shandong; implications for crust-mantle interaction at the edge of the Sulu collisional orogenic belt - Du Qing, Du Qing; Meng Fanchao, Meng Fanchao; Kerr, Andrew C; Chen Yong, Chen Yong; Tian Yulu, Tian Yulu; Wu Zhiping, Wu Zhiping; Zhou Yaoqi, Zhou Yaoqi (Lithosphere, 2022)
We present new whole-rock geochemical, Sr-Nd-Pb isotopic, and zircon U-Pb and Hf isotopic data for Early Cretaceous magmatic rocks (trachy-andesite, pyroxene diorite, diorite porphyrite, and dolerite) in the Wulian area of Shandong, eastern North China. These data are used to constrain the mechanism of crust-mantle interaction at the edge of the Sulu orogenic belt. The belt formed by the collision of the Yangtze Craton (YC) and the North China Craton (NCC) during the Mesozoic. New zircon U-Pb dating indicates that the magmatic rocks were formed during the Early Cretaceous (123-124 Ma). These rocks are characterized by moderate contents of SiO2 (50.0-60.0 wt.%), MgO (3.3-5.6 wt.%), Cr and Ni with low Nb/U ratios (0.8-11.8), and high La/Nb (5.2-24.5) and Ba/La ratios (12.3-38.1). They are enriched in large ion lithophile elements, depleted in high field strength elements, and are characterized by high initial 87Sr/86Sr values (0.7079-0.7088) and low εNd(t) (-20.6 to -14.6). The samples have relatively low initial 206Pb/204Pb (16.38-17.18), 207Pb/204Pb (15.38-15.48), and 208Pb/204Pb (37.24-37.83) values. The Sr-Nd-Pb-Hf isotopic characteristics of the samples are similar to those of mafic rocks in the Sulu orogenic belt, suggesting that they might have similar sources. It is clear that the magma source of the samples involves both crustal and mantle materials and so we propose a model for crust-mantle interaction at the edge of Sulu orogenic belt. In this model, the Yangtze plate subducted deep below the northwestern NCC during the Triassic and was trapped in the lithospheric mantle. In the early Cretaceous, lithospheric extension in combination with asthenospheric upwelling resulted in partial melting of the overlying lithospheric mantle. The magmatic rocks in the Wulian area were generated by mixing between melts of both the lithospheric mantle of the NCC and the residual lower crust of the YC. This study therefore provides significant information on crust-mantle interaction at a continental subduction zone.